Hell: in search of a christian ecology - Morton, Timothy (Columbia University Press, 2024)
"Timothy Morton's aim in Hell is to up the game of ecological theory and praxis, moving away from their data-dumping guilt mode and into the planetary-scale inspirational feel that is the spiritual ecstasy of life itself. Nothing less than such a transformation can convince religious climate-change deniers to give up their passionate beliefs that the comforting support of Jesus can assuage all ills. On Earth hell is marked by the binary of subject/object in all its varieties--gendered, racialized, colonized--all master/slave relationships, the hallmark of capitalism and the Anthropocene--and is evidenced by the twinned theological forms of evangelical religion and scientism. Morton proposes instead that the sacred is the phenomenology of biology--how life from its earliest evolutionary beginnings feels--not subjective inner experience but a way of being in symbiotic relationship, a mood permeating existence. They find resources in visionaries William Blake and Friedrich Nietzsche but also, counterintuitively, in Immanuel Kant, all of whom refused to ontologize science. In hell, by contrast, we are entrapped in the measurable, purposive physical world. Blake above all understood that ideology structures our worlds and that we have to fight hard to change it. The biosphere is driven by unconditioned desire--without a telos--thus queerness, pleasure, beauty, art happen in all conscious (sentient) beings. That surge of life is holy, our birthright, and if not a reason to "save Earth," what could be?"--